Indigeneity, Ethnicity, and the State: Australia, Fiji, and New Zealand - O’Sullivan, Dominic (Nationalism and Ethnic Politics, 2014)
This article draws on the politics of indigeneity to distinguish the claims of first occupancy from simple ethnic identity politics, illustrating that relative political marginalization in Australasia is not so much a function of minority status but of indigeneity itself. The politics of indigeneity's aim is to create political space for self-determination and a particular indigenous share in the sovereign authority of the nation-state itself. The Australasian states are compared with Fiji to demonstrate that the significance of historical constraints on political authority transcend the withdrawal of a colonial power and the restoration of collective indigenous majority population status.

Theorising the structural dynamics of ethnic privilege in Aotearoa: Unpacking “this breeze at my back” - Moewaka Barnes, Helen; Borell, Belinda; Mccreanor, Tim (International Journal of Critical Indigenous Studies, 2014)
Colonial praxis has been imposed on the culture, epistemologies and praxis of indigenous Maori in Aotearoa, entrenching the settler cultural project that ensures the continuation of the colonial state, producing damaging disparities. This article theorises ways in which settler privilege works at multiple levels supporting settler interests, aspirations and sensibilities. In institutions, myriad mundane processes operate through commerce, law, media, education, health services, environment, religion and international relations constituting settler culture, values and norms. Among individuals, settler discursive/ideological frameworks are hegemonic, powerfully influencing interactions with Maori to produce outcomes that routinely suit settlers. In the internalised domain, there is a symbiotic sense of belonging, rightness, entitlement and confidence that the established social hierarchies will serve settler interests. This structure of privilege works together with overt and implicit acts of racism to reproduce a collective sense of superiority. It requires progressive de-mobilising together with anti-racism efforts to enable our society to move toward social justice.
Keywords: belonging; health; inequity; privilege; racism; wellbeing

The Association of Crime Stories and Maori in Aotearoa New Zealand Print Media - McCreanor, Timothy; Rankine, Jenny; Moewaka Barnes, Angela; Borell, Belinda; Nairn, Raymond; McManus, Anna-Lyse (Sites: A Journal of Social Anthropology and Cultural Studies, 2014)
This paper explores associations between crime reporting and Maori ethnicity in a large representative sample of newspaper items gathered in Aotearoa New Zealand between November 2007 and April 2008, using content, thematic and discursive analyses and audience interpretations. The association of Maori and crime was prominent in these newspapers and Maori were frequently labelled as possible or actual perpetrators of crime on superficial judgements, often by victims. This practice associates Maori with all accounts of crime and embeds crime as a background for all other items about Maori. In contrast, newspaper coverage of Pakeha perpetrators of a crime against a Maori organisation worked to valorise the convicted thieves. This embedding of crime as a background to other stories about Maori, the pervasive but unacknowledged Pakeha1 norms, and media positioning of Maori as a threat in non-crime stories, is central to hegemonic discourses of Maori-Pakeha relations. Focus groups participants indicated that these discourses support real-world marginalisation and discrimination against Maori in Aotearoa New Zealand.
Keywords: crime; news media; racism

Reconciliation as Public Theology: Christian Thought in Comparative Indigenous Politics - O’Sullivan, Dominic (International Journal of Public Theology, 2014)
Abstract Christian public theology extends reconciliation beyond its principal sacramental concern for relationships between God and penitent to the construction of ‘socially just’ public relationships for the settlement of intra-national conflict. In theological terms, reconciliation brings public relationships into what Hally calls ‘the Christ narrative of passion, death and resurrection’ in which the perpetrators of injustice repent and seek forgiveness. This article introduces the conflicts that these discourses aim to resolve in Australia, Fiji and New Zealand and explains and contrasts reconciliation’s relative importance in each of these jurisdictions. Moreover, the article’s cross-jurisdictional comparison shows reconciliation’s limits and possibilities as public theology, and argues that in Australia and New Zealand it has helped to create political environments willing to admit indigenous perspectives on a range of policy issues. On the contrary, however, the article also shows that the Fijian churches have distorted the concept of reconciliation to support political imperatives that are difficult to rationalize theologically, even though they are presented by the churches as being concerned with religious goals.
Keywords: christianity; colonisation; kāwanatanga; reconciliation; religion

Opinion: Decriminalise cannabis, decriminalise Maori? - Kaa, Hirini (Matters of Substance, 2014)
That Maori are more often criminalised for cannabis use is often used as another good argument for decriminalisation. But Hirini Kaa argues things are more complex and that, as many Maori probably know, decriminalisation won't be the panacea proposed so often by privileged pakeha.
Keywords: cannabis; decriminalization; discrimination; social conditions

Social identity and differences in psychological and economic outcomes for mixed and sole-identified Māori - Houkamau, Carla A.; Sibley, Chris G. (International Journal of Intercultural Relations, 2014)
Māori are the indigenous peoples of New Zealand and are culturally and ethnically diverse. Previous research suggests that Māori who identify jointly as European (New Zealand's dominant group) may have improved employment outcomes, income and levels of education relative to those who identify solely as Māori. However, research exploring the broader constellation of factors linked to multiple versus sole-ethnic affiliation for Māori remains scarce. We examine differences in outcomes for Māori depending upon their single versus multiple ethnic affiliation as Māori, Māori/European, or European (but with Māori ancestry) in a national probability sample (N=1416). Results indicated that people who identified jointly at Māori/European expressed political attitudes more aligned with Europeans. However, while Māori/Europeans may be more aligned with other Europeans in terms of support for mainstream political parties and intergroup attitudes, they remained lower on various indicators of social and economic status. In this latter regard, Māori/Europeans reported outcomes more similar to their sole-Māori counterparts.
Keywords: ethnicity; health; identity; ideology; wellbeing; whakapapa

Enacting Kaitiakitanga: Challenges and Complexities in the Governance and Ownership of Rongoa Research Information - Boulton, Amohia; Hudson, Māui; Ahuriri-Driscoll, Annabel; Stewart, Albert (The International Indigenous Policy Journal, 2014)
Explore millions of resources from scholarly journals, books, newspapers, videos and more, on the ProQuest Platform.
Keywords: data; indigenous data sovereignty; kaitiakitanga; rangatiratanga

Towards a Social-Structural Model for Understanding Current Disparities in Maori Health and Well-Being - Reid, John; Taylor-Moore, Karyn; Varona, Golda (Journal of Loss and Trauma, 2014)
Colonization has resulted in Maori occupying a vulnerable position in New Zealand society. Comparatively poor health, along with complex social and economic problems, is a reflection of this fundamental insecurity. This article aims to put forward a historical and developmental perspective for understanding some of the current health disparities experienced by Maori, by exploring the concepts of historical trauma, loss of land, and alternative theories of development from post-development theory.
Keywords: colonisation; health; historical trauma; land loss

Fostering sustainable tribal economies in a time of climate change - Bargh, Maria; Douglas, Sarsha-Leigh; Te One, Annie (New Zealand geographer, 2014)
In this article, we explore how Māori tribal organisations are responding to calls by other Indigenous peoples to become more sustainable in a time of climate change. From a close examination of tribal Environmental Management Plans, we move to a specific case study in the Bay of Plenty area, Ngāti Kea/Ngāti Tuara. Ultimately, we suggest that many tribal organisations are seeking to respond to climate change and transition to becoming producers of their own food and energy needs, and are often articulating these responses in relation to specific local resources and contexts.
Keywords: climate change; economic aspects; environmental management; iwi; iwi development; sustainable development